Evaluation of Growth Performance and Economic Efficiency of Hybrid Ducks through Herbal Probiotic Feed Supplementation - David Kurniawan (JAMI: Jurnal Ahli Muda Indonesia, 2025)
Backgrounds. This study aimed to evaluate the effects of herbal probiotic supplementation in duck feed on the production performance and economic viability of hybrid meat ducks. Methods. A total of 500 unsexed hybrid meat ducklings (DOD), obtained from a cross between Peking drakes and Khaki Campbell ducks, were randomly assigned into five treatment groups (100 ducks per replicate). The experiment was conducted over a 6-week period using a completely randomized design (CRD). All ducks were fed a basal diet formulated according to NRC (1994) standards, with herbal probiotics added to the feed as treatments. Performance indicators measured included feed intake, body weight gain, and feed conversion ratio (FCR). Economic analysis included production costs, revenue, net income, break-even point (BEP), income over feed cost (IOFC), income over feed cost and chick (IOFCC), and revenue-to-cost (R/C) ratio. Data was analyzed using descriptive quantitative methods. Results. Herbal probiotic supplementation positively influenced duck growth performance, resulting in an average FCR of approximately 2.00. Economic analysis revealed improved profitability, with an average R/C ratio of 1.26 and favorable IOFC values. These findings indicate that herbal probiotics can enhance nutrient efficiency without increasing production costs. Conclusions. Incorporating herbal probiotics into duck feed is a promising strategy to improve both biological performance and economic returns in commercial duck farming. Further research is recommended to confirm long-term benefits and broader applicability.